PLANT GROWTH RESPONSE ONLY (LACTUCA SATIVA L.) ON MEDIA USING VERMIKOMPOS WASTE CULTIVATION OF MUSHROOM CUSHION - Suhartini Suhartini (Jurnal Penelitian Saintek, 2007)
'l7Iis research  is  done  to  know  the  influences  of  the  maturity vemUcompost level of mushroom cultivated waste on the growth of se/ada, to know the influences of the combination between soil and vermicompost of mushroom cultivated waste on the growth of selada, to know the influences of interaction between vermicompost maturity level and the combination between soil and vermicompost on the growth of selada and to know what the vermicompost of mushroom cultivated waste can be used as organicfertiliser of seiada cultivation. This research is done to know the response of selada crop planted on dijJerentmaturation vermicompost media. The preparation that must be done before areproduce vermicompost and breeding of selada crop and analise ofvermicompost.The dependent variabel of this research is maturation vermicompostlevel (composted during 1month), half maturity (composted duringtwo months) and mature (composted during 3 months). The combination between soil  and compost is 2:1,  3:1  and 4:1.  The independent variabel is the growth of Selada that include wet weight (gram), high of crop (em), number of leaf (piece), and dry weight of crop (gram). The data of the research result of crop growth analysed using completly random design factorial.  When there is a significant different continued with Duncan Multiple Range Test}. The quality of product examined by test quality of crop vegetable.Based on the research result can be concluded  that the maturity vermicompost level of mushroom cultivated waste influences the cropgrowth by using of wet weight, dry weight, number of leaf and high of crop. The maturity vermicompost level give the significant different on all of the independent variable. The maturity level give the best growth. The comparation between soil and vermicompost 2:1; 3: 1; and 4:1; the 3:1 comparation gives the highst value for  wet weight and d weight.  .Whilefor.  the  high  of  crop and  the  number  of  leaf  tZ c~mpartwn  of  SOli   and  vermicompost  dont  give  the  significant difJere~t. Ba~ed on that result the best use ofvermicompost  is 3:1. There.ls n~t interaction between vermicompost maturity level and the combination between soil and vermicompost on the growth of selada. Based on the result of analise the vermicompost and the response of the growth of selada, so that the vermicompost of mushroom cultivated waste can be used as organicfertiliser ofselada.